The Psychological Effects of Park Therapy Components on Campus Landscape Preferences - Pratiwi, Prita Indah; Sulistyantara, Bambang; Sisriany, Saraswati; Lazuardi, Samuel Nanda (Journal of Contemporary Urban Affairs, 2022)
COVID-19 has doubled the prevalence of mental health problems among young adults. In Indonesia, it extends the vulnerability of families, increases economic uncertainty, interrupts food security, and affects psychological well-being. Accordingly, this research examined the correlation between psychological effects and preferred landscape elements. Experiments were conducted in a campus park, arboretum, and a road. Participants captured attractive views during the walk using the Visitor-Employed Photography method and evaluated psychological effects using the Profile of Mood States (POMS) and the State-Trait Anxiety Inventory (STAI) pre-and post-walking. Google Cloud Vision API was used to get the image annotation keywords. The results indicated a correlation between psychological effects and preferred landscape elements. Park therapy components, including plant, flower, and sky, were negatively correlated with negative moods and anxiety levels. These findings presented scientific evidence for the psychological relaxation outcome of walking and prominent components of park therapy to support therapeutic campus greenspace planning.